Evolution of Human-Like Social Grooming Strategies Regarding Richness and Group Size - Takano, Masanori; Ichinose, Genki (Frontiers in Ecology and Evolution, 2018)
Human social strategies have evolved as an adaption to behave in complex societies. In such societies, humans intensively tend to cooperate with their closer friends, because they have to distribute their limited resources through cooperation (e.g. time, food, etc.). It also makes the situation difficult to have uniform social relationships (social grooming) with all friends. Thus, the social relationship strengths often show a much skewed distribution (a power law distribution). Here we aim to show adaptivity of such social grooming strategies in order to explore the evolution of human social intelligence. We use a model in the framework of evolutionary games where the social grooming strategies evolve via building social relationships with cooperators. Simulation results demonstrate four evolutionary trends. One of the trends is similar to the strategy that humans use. We find that these trends depend on three parameters; individuals' richness, group sizes, and the amount of social grooming. The human-like strategy evolves in large poor groups. Moreover, the increase of the amount of social grooming makes the group size larger. Conversely, this implies that the same strategy evolves when the amount of social grooming is properly adjusted even if the group sizes are different. Our results are important in the sense that, between human and non-human primates, the differences of the group size and the amount of social grooming are significant.